1986
DOI: 10.1200/jco.1986.4.5.767
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of intravenous menogaril administered intermittently.

Abstract: Thirty-three adult patients with solid tumors were treated with menogaril, a new anthracycline antibiotic. The drug was given as a two-hour infusion every 4 to 5 weeks at doses ranging from 17 to 250 mg/m2. The maximum tolerated dose was 250 mg/m2. Reversible and dose-related leukopenia was the dose-limiting toxicity. Thrombocytopenia was less frequent. Hematologic toxicity was maximal 2 weeks after treatment, and recovery usually occurred within 4 weeks. There was no dissociation between WBC and neutrophil co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The low incidence of mucositis, nausea and vomiting and alopecia confirms results from previous phase I and early phase II trials [5,9,11]. A greater proportion of patients who had received adjuvant chemotherapy required dose adjustment.…”
Section: Discussionsupporting
confidence: 81%
“…The low incidence of mucositis, nausea and vomiting and alopecia confirms results from previous phase I and early phase II trials [5,9,11]. A greater proportion of patients who had received adjuvant chemotherapy required dose adjustment.…”
Section: Discussionsupporting
confidence: 81%
“…The mechanism of action of menogaril appears unrelated to interaction with DNA [7]. Phase I studies have shown that the major (and dose limiting) toxicity is neutropenia with local phlebitis as the predominant non-hematologic side effect [8]. Phlebitis is decreased by dilution and by rapid infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Phase I trials of the intravenous formulation found myelosuppression to be dose limiting. Local venous toxicity, nausea, vomiting and mild hair loss were also noted [4,5].…”
Section: Introductionmentioning
confidence: 99%